REVIVAL OF TODA EMBROIDERY-NEEDLECRAFT OF NILGIRIS - Garima Sharma; Simmi Bhagat (Fakultas Seni Rupa dan Desain ITB, 2018)
The Toda are an ancient pastoral people who live in the cool uplands of the Nilgiri Mountains of Tamil Nadu, India. Toda women do an aesthetically great and intricate form of embroidery and it holds a cultural uniqueness for the Toda community. This distinct style of embroidery is locally known as